The Impact of Uncertainty Spillover on Cash Holdings Behavior of Turkish Firms - Tan, Omer Faruk; Aksoy-Hazir, Cagri (International Journal of Economics, Management and Accounting, 2022)
This paper examines the impact of the World Uncertainty Spillover Index-United States (WUSI-USA) on cash holdings policy of 211 Turkish firms between 2005 and 2019, applying unbalanced panel data regression strategy. According to the findings, a positive relationship exists between uncertainty spillovers and cash holdings. When faced with uncertainty, firms prefer to restrain cash reserves for a precautionary motive. From the real options perspective, firms delay or postpone their investments under uncertain conditions. In addition, dividend payments, cash flow, tangibility, non-cash working capital, short-term debt, and capital expenditure are major determinants of cash holdings. Finally, under alternative models, we find robust results.